1999
DOI: 10.1023/a:1024762919372
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder and traumatic brain injury: Are they mutually exclusive?

Abstract: It has been suggested that posttraumatic stress disorder (PTSD) and traumatic brain injury (TBI) must be mutually incompatible disorders. However, growing empirical evidence has begun to question this. Evidence suggests that although PTSD may be relatively rare among the TBI population, some TBI patients seem to develop PTSD. We suggest two theoretical routes through which PTSD might develop in TBI patients: through nonconscious processes in individuals who are subsequently amnesic, but who were conscious at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 55 publications
0
27
1
Order By: Relevance
“…44 Prior cross-sectional studies have also reported associations between TBI and PTSD, 45,46 although injury severity may govern the association. 47,48 Higher morbidity and use of medical services are associated with severe TBI, whereas mental Higher CAPS scores may also reflect nonspecific symptoms that overlap with TBI sequelae. Alternatively, perhaps the overall contexts surrounding severe TBI were more emotionally traumatic than contexts surrounding milder injuries.…”
Section: Discussionmentioning
confidence: 99%
“…44 Prior cross-sectional studies have also reported associations between TBI and PTSD, 45,46 although injury severity may govern the association. 47,48 Higher morbidity and use of medical services are associated with severe TBI, whereas mental Higher CAPS scores may also reflect nonspecific symptoms that overlap with TBI sequelae. Alternatively, perhaps the overall contexts surrounding severe TBI were more emotionally traumatic than contexts surrounding milder injuries.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the post-traumatic amnesia associated with TBI may protect against the development of PTSD, based on the notion that amnesia for the event precludes formation of the core affective responses associated with the development of PTSD. 51 Although PTSD can clearly develop after even moderate-to-severe TBIs, one prospective study did find that PTSD rates were higher in subjects who remembered the TBI incident than in those with no memory for the event. 52 The studies reported here, which were conducted using general anesthesia, however, suggest that a blast-related mTBI exposure can induce PTSD-related traits independent of exposure to a PTSD stressor.…”
Section: Figmentioning
confidence: 99%
“…These mechanisms include the islands of memory within the period of PTA [25,49], short or incomplete amnesia [50], memories from before and/or after the actual event [48], implicit unconscious memories [51][52], and memories based on details the individual has later heard or seen about the event [53][54].…”
Section: Influence Of Posttraumatic Amnesiamentioning
confidence: 99%